Evaluation of the Primary Healthcare attributes in a municipality located in the countryside of São Paulo State – Brazil - Fracolli, Lislaine Aparecida; Junko Muramatsu, Marianne; Pereira Gomes, Maria Fernanda; Rodrigues Zequini Nabão, Fabiana (O Mundo da Saúde, 2015)
The Primary Healthcare can be qualified by the existence of four main attributes: access of the individual´s first contact with the healthcare system, longitudinality, integrality, coordination of care and three derivatives: family counseling, com- munity orientation and cultural competence. Therefore, this study aimed to evaluate the existence and the extent of the Primary Healthcare attributes (PH) in the Family Health Strategy (FHS) in the municipality of Quatá-SP. The evaluative and quantitative study collected data through interviews with 34 caregivers who have cared for children under two years old by the use of PCATool child version in January 2014. The Primary Healthcare attributes have been reported as satisfactory; however, the accessibility and available services should improve their workability. This study identified the necessity to improve the population´s access to the Primary Healthcare services. Proper adaptations should be performed during the opening hours of the healthcare centers; facilitating access and appointment scheduling; improve the counter-reference and reference system; offer vaccination and stitch services; and also, improve the communication between professionals and users, review and reformulate the attendance model of the FHS